Dinamika Harga BBM: Dampaknya Terhadap Ekonomi Nasional dan Daya Beli Masyarakat - Edy Soesanto; Thomas Komansilan; Natasha Salsabillah (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
The fluctuation of fuel prices (BBM) significantly impacts the national economy and public purchasing power. This study examines the dynamic relationship between fuel price adjustments, economic growth, inflation, and the socioeconomic conditions of society. The findings reveal that an increase in fuel prices often triggers a domino effect, including rising transportation and production costs, ultimately affecting consumer prices and reducing purchasing power. Conversely, the decline in fuel prices provides a short-term boost to public spending but may challenge government revenue if fuel subsidies increase. Policy recommendations include balancing fuel price adjustments with measures to protect vulnerable groups and maintain economic stability.